The Rose : The Judgment - Book 2 - Lewis, Beverly 1949- (Minneapolis, Minn. : Bethany House, 2011)
Rose Kauffman and her older sister, Hen, struggle to find love, acceptance, and their place in the Amish community.
Keywords: Amish -- Fiction; Pennsylvania Dutch Country (Pa.) -- Fiction; Fiction